The The Effect of Perceived Ease of Use on Repurchase Intention with Perceived Usefulness as an Intervening Variable On Tiket.com - Dzikri Maulidina Putri; Kristina Sisilia (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to determine how much influence perceived ease of use has on repurchase intention through perceived usefulness as an intermediary variable in the Tiket.com business. The Tiket.com application requires customers to continue making purchases through the application by understanding how easy it is to interact and use the application according to their needs. This study uses a quantitative method with the Nonprobability Sampling technique on 200 consumers who have previously used and made transactions on the Tiket.com application. Data analysis techniques used descriptive analysis and Structural Equation Modeling (SEM) analysis using Partial Least Square (PLS). The results of the analysis show that there is a positive and significant influence between perceived convenience on perceived benefits, perceived convenience has a positive and significant effect on repurchase intentions, perceived benefits have a positive and significant effect on repurchase intentions, and the effect of perceived convenience on repurchase intentions through perceived benefits. The R-Square value on the Repurchase Intention variable is 83.3% which can be explained by the Perceived Ease of Use variable and the Perceived Usefulness variable can be explained by 86.3% by the Perceived Ease of Use variable and the rest is influenced by other variables not explained in this study .